Resolution of a hepatoduodenal fistula after nivolumab treatment in a patient with hepatocellular carcinoma: challenges in immunotherapy. Issue 1 (2nd January 2022) - De Somer, Thomas; Vanderstraeten, Erik; Bouderez, Vincent; Monsaert, Els; Van Steenkiste, Christophe
ABSTRACT: Hepatocellular carcinoma is the fourth leading cause of cancer-related death worldwide, with limited treatment options for patients with advanced hepatocellular carcinoma. Beyond standard systemic therapy with multikinase inhibitors, recent studies demonstrate the potential for a robust and durable response with immune checkpoint inhibition in subsets of patients with hepatocellular carcinoma. We present a case of an 83-year-old male patient with the diagnosis of a multifocal hepatocellular carcinoma. A hepatoduodenal fistula developed under treatment with sorafenib which necessitated treatment interruption. Therefore, a switch to second line therapy with immunotherapy nivolumab was made and supportive enteral nutrition was started. This led to a spectacular oncological response, with complete resolution of the hepatoduodenal fistula. To our knowledge this is the first case which describes the involution of a fistula in a hepatocellular carcinoma under treatment with nivolumab.